'Coaching' small biotech companies into success. (21st November 2007) - Luukkonen, Terttu; Maunula, Mari
The paper reports an empirical study on the way Venture Capital organisations (VC here means Venture Capital or the VC organisation) support biotechnology start-ups, not just by providing capital, but through support and advice in strategic management issues, that is, nonfinancial value added. The paper draws attention to differences among assorted types of VC organisations regarding their ways of operating. The study is based on a full population of biotechnology start-ups in Finland and on a survey and interviews with the CEOs of the investee firms. Central findings of the study include an observation that all the investigated VC types did provide value added in the meaning outlined above. Nevertheless, there were clear differences between them in terms of the estimated overall value added as well as in their activity profiles. Informal investors (business angels) were assessed most positively by the CEOs and maintained the closest contacts with their investee firms.